Erythropoietin and thrombopoietin mimetics: Natural alternatives to erythrocyte and platelet disorders. (December 2016) - Gutti, Usha; Pasupuleti, Satya Ratan; Sahu, Itishri; Kotipalli, Aneesh; Undi, Ram Babu; Kandi, Ravinder; Venakata Saladi, Raja Gopal; Gutti, Ravi Kumar
Highlights: Evolution of EPO and TPO recombinant and synthetic mimetics over the years. Limitations with current EPO and TPO mimetics. Current evidence on plant derived products. Plants showing promising results in certain erythrocyte and platelet disorders. Abstract: Erythropoietin (EPO) and thrombopoietin (TPO) plays a major role in the regulation of hematopoietic development. Though, blood transfusion was the most widely used method to treat low blood count, over the years with advancements in recombinant technology and drug designing, the EPO and TPO mimetics are dominating the therapeutics industry. On the other hand, the recombinant human EPO and TPO are associated either with reduced half-life or immune reactions. The restoration of alternate medicine in recent years has the hope to overcome limitations associated with recombinant technology, to treat various disorder including blood diseases, with low to no side effects. The work in recent years on plant derived mimetics suggests a paradigm shift in the way diseases are treated. Here, we are providing a comprehensive review on the EPO and TPO recombinant counterparts and synthetic mimetics studied till date with a focus on the need for more natural alternatives.